Measuring the quality of hotel services using the Servqual model Field study on some four-star hotels - Meziani, Noureddine; Achour, Imane (Dirassat Journal Economic Issue, 2016)
This study aims tomeasure the quality ofservicesofthe AlgerianHotelsFour Starclassusing Servqual model,andthisfrom the viewpoint ofcustomers,To achieve theobjective of the studyand test thepremisequestionnairewasdesignedand distributed toa sample of200customersof thefour selectedhotelsthe eastAlgerianregion, of which 102wereretrievingquestionnaire. The study concludedthe conclusion thatthe perceivedservice quality is better-than-expected level service quality in the hotels under study,This means thatservicequality is satisfactory ; the study, alsoindicatedsome shortcomingsrelated tothe quality ofthe hotel staffunder studyand as well asdeficiencies inthe performance ofsomeessential services such ase-services.